From trustworthy AI to technical standards : The distinctive European approach to artificial intelligence regulation - Gornet, Mélanie (Institut polytechnique de Paris, 2025)
L'Europe a été à l'avant-garde de l'éthique de l'intelligence artificielle (IA), en élaborant des chartes et des principes non contraignants sur l'IA « digne de confiance ». Le terme « digne de confiance » est utilisé par l'Europe pour désigner les systèmes d'IA qui sont « éthiques », « légaux » et « techniquement robustes ». L'Europe a complété ces principes non contraignants par un texte de loi sur l'IA, connu sous le nom de règlement sur l'IA, ou AI Act. Le règlement sur l'IA est l'un des premiers cadres légaux au monde à réglementer les systèmes d'IA dans différents secteurs et cas d'utilisation, en mettant l'accent sur la sécurité et la protection des droits fondamentaux. Pour les questions opérationnelles, le règlement sur l'IA s'appuie principalement sur des normes techniques en cours d'élaboration. L'approche européenne combine donc trois niveaux d'instruments réglementaires : les chartes éthiques de l'IA, le règlement sur l'IA et les normes techniques.L'approche par la normalisation est traditionnelle dans le domaine de la sécurité des produits, mais dans le règlement sur l'IA, les normes sont également censées répondre aux préoccupations en matière de droits fondamentaux. Pour éviter de faire des choix normatifs difficiles, les organismes de normalisation jouent la carte de la sécurité en élaborant des normes qui restent à un niveau élevé. De plus, dans le cadre du règlement sur l'IA, la responsabilité de l'élaboration des normes techniques est déléguée à des organismes de normalisation privés, où les grandes entreprises multinationales sont surreprésentées et exercent une influence considérable. Ces normes sont également généralement payantes, bien que la situation puisse évoluer dans les années à venir après une récente jurisprudence de la Cour de justice de l'Union européenne. Les experts en normalisation sont donc sous pression pour fournir des normes à temps et de bonne qualité. Europe has been at the forefront of Artificial Intelligence (AI) ethics, developing non-binding charters and principles on "trustworthy'' AI. The term "trustworthiness'' is used by Europe to designate AI systems that are "ethical'', "legal'' and "technically robust''. Europe has supplemented these non-binding principles with a binding regulation on AI, known as the AI Act. The AI Act is one of the world's first comprehensive frameworks for regulating AI systems across different industries and use cases, focusing on safety and protection of fundamental rights. The AI Act relies, for operational questions, mostly on technical standards that are in the course of development. The European approach thus combines three layers of regulatory instruments: AI ethics charters, the AI Act and technical standards.The standardisation approach is traditional in product safety, but under the AI Act, standards are also expected to address fundamental rights concerns. To avoid making hard normative choices, standardisation organisations are playing it safe, developing standards which remain at a high-level. Moreover, under the AI Act, the responsibility for developing technical standards is delegated to private standardisation bodies, where large multinational companies are over-represented and hold significant influence. These standards are also often locked behind paywalls, although the situation may evolve in the coming years after a recent case law from the Court of Justice of the European Union. Standardisation experts therefore face pressures to deliver standards on time and of good quality.
Keywords: AI Act; Apprentissage machine; Artificial Intelligence; Ethics; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Machine learning; Normes techniques; Regulation; Règlement IA; Régulation; Technical standards; Éthique

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

Optimising regulatory responses to consumer disempowerment over personal data in the digital world - D'Amico, Alessia (European University Institute, 2021)
This thesis addresses the problem of individuals’ lack of control over personal data in the digital world. It sheds light on market and regulatory failures that lie behind the status quo and proposes a framework to improve regulatory responses. The two regulatory regimes that are at the core of this thesis are EU data protection regulation, which protects individuals’ fundamental rights over data, and EU competition law, which safeguards the sound functioning of the market and consumers’ economic interests. Despite the existence of these two regulatory regimes, individuals do not have sufficient control over personal data collected by digital firms, whose control over large datasets is a factor contributing to market monopolisation. The thesis argues that one reason for the shortcomings of today’s regulatory framework is that the market failure is composed of a combination of factors, which are currently addressed by the different regimes relatively independently. This dichotomy hinders the development of an effective strategy to tackle the market failure in its entirety. The approach taken in this thesis is that by integrating the two regimes, it might be possible to close the gaps deriving from a narrow perception of their regulatory spaces. Hence, the thesis formulates a holistic approach, encompassing data protection regulation and competition law, designed to increase the effectiveness of the regulatory framework as a whole. Different dimensions of the regimes’ interrelation are analysed, to uncover new ways to harness their complementarity and minimise their inconsistencies and overlaps. The thesis looks at how the regimes can incorporate elements from each other to inform their policies and application of their rules, as well as developing a complementary enforcement strategy. The holistic framework ultimately allows both regimes to better tailor their regulatory responses to the functioning of the digital market and take account of the diverse elements that constitute the market failure they seek to correct.
Keywords: Data Protection; Personal data; Privacy

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework

Internet regulation and development: the battle over the network neutrality - Melo, Lílian Manoela Monteiro Cintra de (Universidade de São Paulo, 2018)
We have arrived at crossroads in the debates about the future of the internet governance. It is high time to address the reasons why policy choices have not been sufficient to preserve the internet\'s promise to bring about development, democratic engagement, and social justice. The network neutrality is central to this debate since it intersects all internet layers and is related to most contemporary issues that will shape future of the internet. My assumption is that network neutrality\'s failures are not an unintended consequence of the regulatory system, but part of the problem. My core hypothesis is that network neutrality\'s limits mainly occur because of, first, its inability to secure all envisioned goals and, second, its decontextualized focus on innovation on the last mile of the internet distributional chain. The network neutrality debate has produced a wide variety of work embedded within economic and legal studies regarding what would be necessary to guarantee a free and innovative internet. Although this work has been often disguised under the mask of technique, it is widespread influenced by the evolutionary economics and denies the network neutrality's effects on ongoing struggles for social and economic justice. My proposition is that network neutrality debate has failed because it proved unable to address the problems related to concentrated power structures on the internet and increasing inequalities. To achieve this objective, this dissertation investigates the network neutrality debate over the last decades to identify processes and mechanisms by which its sterile arrangements came to take specific form in time and place, focusing on what such arrangements might inform about contemporary policy efforts. In Chapter 1, prevalent internet governance myths are deconstructed, presenting how specific architecture design and the corresponding network neutrality outcomes came to prevail in particular periods. Drawing upon and integration of distinct source materials, Chapters 2 and 3 identify the specific contingencies over the past decades by which a dynamic set of evolving actors, events, and institutions converged (or not) and gave rise to current network neutrality rules and dissent in the United States and Brazil. At the center of the analysis is the identification of structures and power struggles. Finally, Chapter 4 aims at presenting a new framework towards the network neutrality debate and its potential distributive effects in the global economy, taking technology not as deterministic but embedded and being embedded in all the building blocks of what we term the social.
Keywords: Economic power; ICT; Inequality; Innovation; Internet access; Internet governance; Law and development; Network neutrality; S&TS; Structure

Location data and human mobility : an evaluation of a dissonance that frames data protection and privacy rights - Andrew, Jonathan (European University Institute, 2018)
With citizens’ movements mediated by many technologies that aid our navigation the potential for omnipresent surveillance may potentially institute fundamental changes to the human condition. Locational privacy is pivotal in developing inter-personal associations and relational ties with others and its function is therefore complex, rather than solely affording a degree of independence from the observations made by others. In this respect, a more nuanced understanding of the utility of location data is required; the current hierarchy that delineates personal data from special categories of personal data does not adequately appreciate the capacity for location data to act as a proxy for other sensitive personal data. Furthermore, the binary distinction that reflects the conceptualisation of the right to privacy as a negative right, with related concepts such as identity and personality formation viewed as positive constructs, is increasingly difficult a notion to preserve. The classification and terminology of technologies can illustrate how terms and legal metaphors are developed and applied so as to bridge gaps in applying existing context and precedent. Though the designation ‘location data’ once constituted a reasonable accommodation in nomenclature as an intelligible and easily comprehensible term, even while constituting a significant oversimplification of the data it represented, technological advances have rendered the term increasingly problematic. This study asks whether the existing legal framework at the regional level in Europe is apt to provide sufficiently cogent and coherent regulation given recent developments in technologies. The review analyses the risks associated with this predilection in data processing activities that allows for the identification of ever more intimate and nuanced details of a citizen’s life, behaviours and convictions through the analysis of their location data; in turn, it shall discern the necessity of considering the resulting impacts on citizens’ fundamental rights to privacy and personal data protection.
Keywords: Data Protection; European Union countries; Location data; Privacy

Legal risk and compliance risk in the banking industry in South Africa - Terblanché, Janet René (North-West University, 2013)
The Basel Committee on Banking Supervision has defined operational risk, legal risk and compliance risk. However, the definitions might not be adequate for countries with a hybrid legal system, such as South Africa. This study aims to provide a practical solution to the problems faced by countries with a hybrid legal system wishing to comply with the Basel Committee’s standards. It is argued that compliance, compliance risk and regulatory risk should all be viewed as constituent components of legal risk, and in turn necessarily also of operational risk in a hybrid legal system. Legal risk is a wide concept which includes all aspects of a legal system, while compliance risk is a narrower concept which only includes the codified aspects of a legal system. Legal risk therefore includes compliance risk. However, the opposite is not true as compliance risk does not include legal risk, and the two concepts are decidedly shown not to be synonymous in a mixed legal system.
Keywords: Basel Committee; Compliance; Compliance risk; Legal compliance; Legal risk; Operational risk; Regulatory compliance; Regulatory risk

The Protection of Privacy in the Workplace: A Comparative Study - Gondwe, Mimmy (Stellenbosch University, 2011)
The importance of privacy lies in the fact that it represents the very idea of human dignity or the preservation of the ‘inner sanctum’. Not surprisingly, however, operational concerns of employers and technological developments combine continuously to challenge the preservation of privacy in the workplace. Employees the world over are exposed to numerous privacy invasive measures, including drug testing, psychological testing, polygraph testing, genetic testing, psychological testing, electronic monitoring and background checks. Hence, the issue at the heart of this dissertation is to determine to what extent privacy is protected in the South African workplace given advancements in technology and the implications (if any) for the right to privacy as such. A secondary aim of the dissertation is to attempt to provide a realistic balance between the privacy concerns of employees and the operational needs of employers in this technological age. As such the main focus of dissertation falls within the sphere of employment law. In order to provide an answer to the research issue discussed above, the dissertation addresses five ancillary or interrelated issues. First, the broad historical development of the legal protection of privacy is traced and examined. Second, a workable definition of privacy is identified with reference to academic debate and comparative legislative and judicial developments. Third, those policies and practices, which would typically threaten privacy in the employment sphere are identified and briefly discussed. Fourth, a detailed evaluation of the tension between privacy and a number of selected policies and practices in selected countries is provided. More specifically, the dissertation considers how these policies and practices challenge privacy, the rationale for their existence and, if applicable, how these policies and practices – if necessary through appropriate regulation – may be accommodated while simultaneously accommodating both privacy and the legitimate concerns of employers. The selection of these practices and policies is guided by two considerations. At the first level the emphasis is on those challenges to privacy, which can be traced back to technological developments and which, as such, foster new and unique demands to the accommodation of privacy in the workplace. The secondary emphasis is on those policies, which are representative of the fundamental challenges created by new technologies to privacy. To effectively address the above issues the dissertation uses the traditional legal methodology associated with comparative legal research, which includes a literature review of applicable law and legal frame work and a review of relevant case law and a comparative study of selected foreign jurisdictions.
Keywords: Privacy infringements; Privacy protection; Right of privacy